2018
DOI: 10.1080/15548627.2018.1474995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRAF6 ubiquitin-ligase activity by PRDX1 leads to inhibition of NFKB activation and autophagy activation

Abstract: 3-MA: 3-methyladenine; BECN1: beclin 1; CHUK/IKKA: conserved helix-loop-helix ubiquitous kinase; ECSIT: ECSIT signalling integrator; ELISA: enzyme-linked immunosorbent assay; NFKB: nuclear factor kappa-light-chain-enhancer of activated B cells; IB: immunoblotting; IKBKB/IKKB: inhibitor of nuclear factor kappa B kinase subunit beta; IL1B: interleukin 1 beta; IL6: interleukin 6; IP: immunoprecipitation; LPS: lipopolysaccharide; MAP1LC3/LC3: microtuble associated protein 1 light chain 3; MAP3K7/TAK1: mitogen-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
175
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 47 publications
9
175
0
Order By: Relevance
“…Moreover, we found that p-IκBα and p-p65 were highly expressed and that IκBα was detected at low levels in BV2 cells after LPS treatment: Ala inhibited the degradation of IκBα but had no significant effect on p65. The p65 subunit of the activated NF-κB translocated from the cytoplasm to the nucleus, where it induced the expression of downstream target genes, including COX-2, iNOS, IL-1β, and IL-6 [44,45]. Increasingly, more research has demonstrated that the NF-κB p65 subunit is primarily retained in the cytoplasm of unstimulated BV2 cells but translocates to the nucleus when these cells are stimulated with LPS [32,46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that p-IκBα and p-p65 were highly expressed and that IκBα was detected at low levels in BV2 cells after LPS treatment: Ala inhibited the degradation of IκBα but had no significant effect on p65. The p65 subunit of the activated NF-κB translocated from the cytoplasm to the nucleus, where it induced the expression of downstream target genes, including COX-2, iNOS, IL-1β, and IL-6 [44,45]. Increasingly, more research has demonstrated that the NF-κB p65 subunit is primarily retained in the cytoplasm of unstimulated BV2 cells but translocates to the nucleus when these cells are stimulated with LPS [32,46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can enhance bactericidal activity and inhibit the invasion and migration of tumor cells. 17 Among the proteins identified by proteomics for ESCC, PRDX1 is considered a tumor-associated antigen for EC cells. In the present study, PRDX1 was shown to be a tumor suppressor gene that is highly expressed in three ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of ubiquitination of EZH2 is complex, and several E3 ligases, such as Smurf2, β-TrCP, Praja1 and FOXP3, have been reported to be involved in these processes [37][38][39][40]. TRAF6 is a kind of adaptor protein and E3 ubiquitin ligase that belongs to the family of tumor necrosis factor receptorassociated factors (TRAFs), and plays a vital role in various solid tumors through activating multiple signaling pathways [41,42]. Recent study showed that TRAF6 could catalyze K63-linked polyubiquitination of EZH2 and promote its proteasome-dependent degradation in prostate cancer [26].…”
Section: Discussionmentioning
confidence: 99%